Deathrow - Garcia, Eddie; Domingo, Cogie; Jose, Jacklyn
"Sonny is an unloved orphan raised in the slums of Manila. Pressured by his friends, he resorts to thievery. During one heist, his friend accidentally kills an old woman. When the police arrive, Sonny gets arrested. A minor unable to prove his innocence, he was convicted for murder and sent to prison. Inside Deathrow, he is welcomed to the cruel and horrifying world of his inmates. But among these hardened souls is a gruff old man who takes Sonny under his wing. He is Sinat, Sonny's protector and savior inside prison"--https://www.imdb.com/title/tt0294514/plotsummary?ref_=tt_ov_pl